2022
DOI: 10.1186/s12913-022-08710-y
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors associated with the prevalence of knowledge, attitude, and practice in seeking skilled maternal healthcare services among women in a remote area of Gesha district

Abstract: Background Skilled health care is essential for the mother's and newborn's health and well-being during pregnancy, labor, and the postpartum period. This study aimed to analyze women's knowledge, attitudes, and practices while requesting competent assistance for maternity healthcare in Gesha District, Southwest Region of Ethiopia. Methods A community-based cross-sectional study design was conducted from September 20, 2021 to October 19, 2021. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The other determinants of PNC knowledge reported in this review include the number of previous pregnancies (Beraki et al, 2020;Yaya Tessema, et al, 2023;Leta, 2022;Berhan & Gulema, 2018;Mose et al, 2021;Kebede et al, 2020;Yitayew et al, 2021;Roney et al, 2021;Kanu et al, 2014;Meseka et al, 2017), whether the pregnancy was planned or not (Hassen & Lelisho, 2022;Kebede et al, 2020), family size (Tesfaye et al, 2022), whether the woman stayed with the father of the baby (Tesfaye et al, 2022;Nchimbi & Joho, 2022), involvement of the father of the baby in PNC activities (Kebede et al, 2020;Roney, et al, 2021), and whether the woman had self-decision making power to seek care for herself and her baby (Yaya Tessema et al, 2023). All the studies that reported on the number of pregnancies as a determinant of PNC knowledge (Beraki et al, 2020;Yaya Tessema et al, 2023;Leta, 2022;Berhan & Gulema, 2018;Mose et al, 2021;Kebede et al, 2020;Yitayew et al, 2021;Roney et al, 2021;Kanu et al, 2014) revealed that women who had more children were more likely to have PNC knowledge compared to those who had fewer, except for one (Meseka et al, 2017) that revealed that primiparous women were more likely to have good PNC knowledge compared to multiparous women.…”
Section: Review Findingsmentioning
confidence: 95%
See 4 more Smart Citations
“…The other determinants of PNC knowledge reported in this review include the number of previous pregnancies (Beraki et al, 2020;Yaya Tessema, et al, 2023;Leta, 2022;Berhan & Gulema, 2018;Mose et al, 2021;Kebede et al, 2020;Yitayew et al, 2021;Roney et al, 2021;Kanu et al, 2014;Meseka et al, 2017), whether the pregnancy was planned or not (Hassen & Lelisho, 2022;Kebede et al, 2020), family size (Tesfaye et al, 2022), whether the woman stayed with the father of the baby (Tesfaye et al, 2022;Nchimbi & Joho, 2022), involvement of the father of the baby in PNC activities (Kebede et al, 2020;Roney, et al, 2021), and whether the woman had self-decision making power to seek care for herself and her baby (Yaya Tessema et al, 2023). All the studies that reported on the number of pregnancies as a determinant of PNC knowledge (Beraki et al, 2020;Yaya Tessema et al, 2023;Leta, 2022;Berhan & Gulema, 2018;Mose et al, 2021;Kebede et al, 2020;Yitayew et al, 2021;Roney et al, 2021;Kanu et al, 2014) revealed that women who had more children were more likely to have PNC knowledge compared to those who had fewer, except for one (Meseka et al, 2017) that revealed that primiparous women were more likely to have good PNC knowledge compared to multiparous women.…”
Section: Review Findingsmentioning
confidence: 95%
“…All the articles reported on quantitative cross-sectional studies. Sixteen of the articles were from studies conducted in Ethiopia (Beraki et al, 2020;Yaya Tessema et al, 2023;Leta, 2022;Berhan & Gulema, 2018;Getachew et al, 2022;Berhea et al, 2018;Mose et al, 2021;Hassen & Lelisho, 2022;Mekonnen et al, 2021;Seifu et al, 2020;Guta et al, 2020;Kebede et al, 2020;Tesfaye et al, 2022;Yitayew et al, 2021;Bulto et al, 2019;Degefa, et al, 2019), two each in Kenya (Kiragu et al, 2021;Roney et al, 2021), Tanzania (Msiba et al, 2022;Nchimbi & Joho, 2022), and Rwanda (Batamuriza & Uwingabire, 2020;Deynu & Nutor, 2023), and one each in Sierra Leone (Kanu et al, 2014), Zambia (Chembe & Siziya, 2017), and South Sudan (Meseka et al, 2017). Eight of the articles (Mose et al, 2021;Guta et al, 2020;Kebede et al, 2020;Tesfaye et al, 2022;Yitayew et al, 2021;Bulto et al, 2019;Degefa, et al, 2019;Roney et al, 2021) reported on studies that researched on knowledge of neonatal danger signs (NDS), seven (Leta, 2022;Berhan & Gulema, 2018;Getachew et al, 2022;Berhea, et al, 2018;Msiba, et al, 2022;…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations